The Effect of Financial Knowledge and Income on Pension Fund Planning Behavior with Locus of Control as A Mediation Variable - Alien Nuril Wardani; Mellyza Silvy (Universitas Kristen Petra dan Ikatan Sarjana Ekonomi Indonesia Cabang Surabaya, 2025)
This study aims to examine the influence of financial knowledge and income on retirement planning behavior with locus of control as a mediation variable. The study included 321 respondents who met criteria such as having a total family income of at least IDR 4.000.000 per month, having worked for at least 2 years, living in Surabaya, Gresik, or Sidoarjo, and having financial management responsibilities in the family. The data analysis technique uses Partial Least Squares Structural Equation Modeling (PLS-SEM) with PLS 6.0. This study finds that financial knowledge and income positively influence retirement planning behavior, and that locus of control can mediate their effects.